Immediate radical fang mark ablation may allow treatment of japanese viper bite without antivenom - Fujioka,M (2009)
Administration of antivenom is currently the standard treatment for snake envenomation. However, it can sometimes cause anaphylactic reactions including urticaria, bronchospasm and hypotension. Furthermore, it may also provoke life-threatening complications, even though the mortality rate is less than 1%. In this study, we present a new treatment - immediate radical fang mark ablation - that was successfully performed on five victims of Japanese viper bites without antivenom use. In these five victims of venomous snakebites, surgical debridement was immediately performed. Two patients received a free-skin graft to resurface their wounds while three of them healed conservatively (i.e. by ointment treatment without surgery). After treatment, all patients could return to work. Immediate radical ablation is a recommended procedure that can reduce the amount of venom in tissues, which consequently decreases inflammatory reactions and reduces the necessity for antivenom.